Design And Implementation Of Network Security System Using Network Management System (NMS) And Firewall On SMA N 1 Bengkulu City - Saputra, Tommy Ade; Khairil, Khairil; Rohmawan, Eko Prasetiyo (Jurnal Media Computer Science, 2023)
This research is entitled Design and Implementation of Network Security System Using Network Management System (NMS) and Firewall at SMA N 1 Bengkulu City. Aims to build a computer network system using linux ubuntu server by setting squid and webmin as a graphical user interface (GUI). Where in doing network management Squid works well including being able to limit accessible website addresses, IP Address management of network users and ports that can or cannot be accessed. The GUI is being used by webmin, because the webmin interface is easy to use. In limiting website addresses, network users' IP addresses and ports that cannot be accessed are done manually via Squid. Linux operating system ubuntu server 20.04 is very good in running Network Management System (NMS) and Firewall because it can be installed or added other tools such as squid and webmin, linux ubuntu server 20.04 in running Network Management System (NMS) and Firewall does not require resources great hardware.